International Law Review in the Assassination of General Qasem Soleimani - Yulianti, Dina; Sidik, Hasan; Mu'min, Mu'min (Indonesian Journal of International Law, 2021)
International law is formed by the global community to establish legal rules, norms, and standards of behavior between sovereign nations to create a peaceful world order. However, since the world order is anarchy with no supreme executive authority, obedience and disobedience to international law often depends on the state’s power. For instance, the assassination of General Qasem Soleimani, a prominent Iranian general, by the US military in Iraqi territory sparked a debate about international law. This article shows that the US action violated International Humanitarian Law (IHL) and International Human Rights Law (IHRL). Additionally, it violated the UN Convention for the Suppression of Terrorist Bombings and Convention on the Prevention and Punishment of Crimes against Internationally Protected Persons, including Diplomatic Agents. These arguments are based on the unproven claims of self-defense and imminent attack and violation of necessity and proportionality. Furthermore, the US committed limited state terrorism based on its behavior characteristics in this case.